Competition in Taxes and IPR - Ronald B. Davies; Yutao Han; Kate Hynes; Yong Wang (University College Dublin, UCD Centre for Economic Research, 2020)
We examine competition for foreign direct investment when governments compete in tax incentives along with intellectual property rights (IRPs) protection. Higher IPRs result in a lower probability of the multinational enterprise (MNE) being imitated and thus higher expected profits and tax revenues, all else equal. We show that, from the perspective of competing hosts, equilibrium IPRs are too high while taxes are too low. Coordination between jurisdictions can therefore lower the multinational's expected payoff, providing a rationale for why during recent trade negotiations FDI home countries complain about low IPRs in some locations while not pushing for them to be centrally determined.
Keywords: F23; H25; O34; 330; Tax competition; FDI; IPRs; Imitation